Artists' SoHo : 49 episodes of intimate history - Kostelanetz, Richard (Empire State Editions, an imprint of Fordham University Press, 2014)
"During the 1960s and 1970s in New York City, young artists exploited an industrial wasteland to create spacious studios where they lived and worked, redefining the Manhattan area just south of Houston Street. Its use fueled not by city planning schemes but by word-of-mouth recommendations, the area soon grew to become a world-class center for artistic creation--indeed, the largest urban artists' colony ever in America, let alone the world"--Provided by publisher.